2D Resistive Switching Memories: Graphene and Related Materials for Resistive Random Access Memories (Adv. Electron. Mater. 8/2017). (August 2017) - Hui, Fei; Grustan‐Gutierrez, Enric; Long, Shibing; Liu, Qi; Ott, Anna K.; Ferrari, Andrea C.; Lanza, Mario
Abstract : Graphene and related materials, such as graphene oxide, hexagonal boron nitride, transition metal dichalcogenides and black phosphorous, are promising candidates for the fabrication of resistive random access memories (RRAM), a technology which could represent the next generation of non‐volatile computer memory. In article number1600195, Mario Lanza and co‐workers explore this emerging field; they discuss, classify, and evaluate a number of materials candidates, and summarize the performance of a number of RRAM prototype devices based on these materials.